(untitled) (Fiep Bulletin - online, 2015)
The old age phase can increase the chances of the emergence of several noncommunicable diseases, having as a shared risk factors, among others, the physical inactivity. The aim of the study is to analyze the practice and level of physical activity of elderly residents in the Canindé city, central backwoods of Ceará State. It is a quantitative study, transversal, domiciliary based, using primary and objective data. The proportional stratified sampling reached a sample of 372 individuals, of a population of 5214 elderly. We used a characterization questionnaire, covering sociodemographic aspects, health perception and practice of physical activities, the International Physical Activity Questionnaire - IPAQ. It was made a database in the SPSS software, version 16.00, to descriptive and inferential statistics, adopting a significance level of 5%. It was found that most seniors is female, aged between 60-69 years old, married and does not practice physical activity. Concerning the level of physical activity, the most are sedentary (58.9%). Regarding the perception of health the majority (76.3%) considers it as "good". Statistically significant diferences were found between the ranges of age and physical activity level (p <0.01) and physical activity (p <0.01). Note the necessity of health strategies aimed at orientation and awareness of healthy behaviors such as physical activities.